2013
DOI: 10.3758/s13421-013-0333-6
|View full text |Cite
|
Sign up to set email alerts
|

Visual working memory declines when more features must be remembered for each object

Abstract: The article reports three experiments investigating

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
123
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(133 citation statements)
references
References 41 publications
10
123
0
Order By: Relevance
“…They noted that past research has largely focused on the nature of underlying limits that restrict the amount and quality of content that the system can store and that the nature of the content itself has had less attention. There is clearly some agreement about the importance of this issue as there is a growing VWM literature illustrating the complexities of the representations and processing involved (Bae, et al, 2014, Bae et al 2015Brady, Konkle, Alvarez, & Oliva, 2013;Oberauer & Eichenberger, 2013;Vergauwe, & Cowan, 2015).…”
Section: Representations Subtending Performancementioning
confidence: 99%
“…They noted that past research has largely focused on the nature of underlying limits that restrict the amount and quality of content that the system can store and that the nature of the content itself has had less attention. There is clearly some agreement about the importance of this issue as there is a growing VWM literature illustrating the complexities of the representations and processing involved (Bae, et al, 2014, Bae et al 2015Brady, Konkle, Alvarez, & Oliva, 2013;Oberauer & Eichenberger, 2013;Vergauwe, & Cowan, 2015).…”
Section: Representations Subtending Performancementioning
confidence: 99%
“…Generally, the number of elements that can be bound together within one synchronous oscillation is not limited. However, an increasing number of elements maintained for one binding slightly decreases the model's capacity (e.g., 7% of capacity is dropped between maintenance of four-element and two-element items), contrary to Vogel et al's (2001) data, but consistently with more recent observations (Oberauer & Eichenberger, 2013).…”
Section: The Present Modelmentioning
confidence: 54%
“…At the same time, the number of features bound does not affect the chance of spurious synchronizations. Accordingly, the authors have found empirical evidence that WM capacity is little affected by the number of features per object (but for the opposite evidence see Cowan, Blume, & Saults, 2013;Oberauer & Eichenberger, 2013), while the number of to-be-maintained objects heavily impacts performance. A similar idea of the temporary binding of features was realized computationally by Raffone and Wolters (2001), who, like Usher (1991, 1992), showed that five or less items may be the natural limit of the model's capacity.…”
Section: Oscillatory Models Of Wm and Reasoningmentioning
confidence: 95%
“…At one time, it was believed that adults’ working memory representations of objects include all of the objects’ physical features, inasmuch as participants could attend to 4 features of the objects with the same performance level as a preselected 1 feature of those same objects (Luck & Vogel, 1997). However, several studies have failed to replicate that finding, instead showing that memory of features is somewhat independent (Wang, Cao, Theeuwes, Olivers, & Wang, 2016) or that memory of any one kind of feature from multi-featured objects in an array (e.g., color) comes at the expense of memory for another kind of feature (e.g., shape) (Cowan et al, 2013; Hardman & Cowan, 2015; Oberauer & Eichenberger, 2013). …”
Section: Development Of Working Memory Capacity In Infancymentioning
confidence: 99%